1976
DOI: 10.1111/j.1471-0528.1976.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperextension of the Fetal Head in Breech Presentation: Radiological Evaluation and Significance

Abstract: Summary Damage of the cervical cord is not rare in breech delivery with hyperextension of the fetal head. Among 57 cases from the literature and one of ours in which the angle of extension could be measured on X‐ray films, 20 had an extension angle greater than 90°. Of these, 11 were delivered vaginally and included 8 cases of damage to the cervical cord. It is recommended that elective Caesarean section be performed when the angle of extension exceeds 90°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Caterini et a1 (1975) in a survey of the literature formed the opinion that an X-ray examination of all breech presentations in early labour was necessary, not only for pelvimetry but also to determine the attitude of the fetal head and suggested that, in cases of hyperextension of the fetal head, Caesarean section should be the management of choice. Several other authors are of the same opinion (Hellstrom and Sallmander, 1968;Bhagwanini et al, 1973;Ballas and Toaff, 1976;Daw, 1976). However, a different opinion has been expressed by Stern and Rand (1959) and Behrman (1962).…”
Section: Discussionmentioning
confidence: 91%
“…Caterini et a1 (1975) in a survey of the literature formed the opinion that an X-ray examination of all breech presentations in early labour was necessary, not only for pelvimetry but also to determine the attitude of the fetal head and suggested that, in cases of hyperextension of the fetal head, Caesarean section should be the management of choice. Several other authors are of the same opinion (Hellstrom and Sallmander, 1968;Bhagwanini et al, 1973;Ballas and Toaff, 1976;Daw, 1976). However, a different opinion has been expressed by Stern and Rand (1959) and Behrman (1962).…”
Section: Discussionmentioning
confidence: 91%
“…9,11 Of gravest concern is the vaginal delivery of a breech fetus with a hyperextended head (ultrasound-measured angle of less than 90 degrees between the cervical vertebrae and the tangent plane of the occipital bone), which occurs in 11% to 15% of breech fetuses and was associated with cervical cord damage in 8 of 11 cases delivered vaginally versus 0 of 20 fetuses delivered by cesarean section. 21 Abroms et al 22 reported a 21% incidence of cervical cord transection among 88 neonates born with hyperextension of the head associated with breech and transverse presentations. All neonates with cord transection were delivered vaginally, whereas none of the neonates delivered by cesarean section suffered permanent spinal cord transection.…”
Section: Other Complications Of Breech Presentationmentioning
confidence: 99%
“…33 Entrapment of the fetal head in an incompletely dilated cervix is a complication specific to breech delivery, however, usually in deliveries remote from term. 36 In one report, 5 of 26 vaginally born infants with hyperextended neck had neurological sequelae, referable to spinal, supraspinal or cerebellar injuries, whereas none of seven delivered by CS had any injury (p = 0.6). An increased risk of birth trauma, including brachial plexus injury at vaginal breech delivery has been reported.…”
Section: Breech Deliverymentioning
confidence: 96%
“…An increased risk of birth trauma, including brachial plexus injury at vaginal breech delivery has been reported. 36,37 Exposure of the umbilical cord to compression or prolapse, and the risk of entrapment of the fetal head and shoulders are two of the explanations for the associations noted in some studies between breech delivery and indicators of hypoxia, including low Apgar scores, 9,38,39 and acidemia at birth, 40 and with neonatal mortality. 36 In one report, 5 of 26 vaginally born infants with hyperextended neck had neurological sequelae, referable to spinal, supraspinal or cerebellar injuries, whereas none of seven delivered by CS had any injury (p = 0.6).…”
Section: Breech Deliverymentioning
confidence: 99%
See 1 more Smart Citation